A Quantitative Evaluation of India’s Commodity Trade Potential with Other SAARC Economies - Islam, Md. Kamrul; Hoque, Ariful; Rajab, Mudasir (Arthshastra Indian Journal of Economics & Research, 2024)
Purpose : This study examined the intensity of trading relationships between India and other South Asian Association for Regional Cooperation (SAARC) economies. It also evaluated the extent to which SAARC economies’ trade complemented one another and investigated the potential for commodity trade between India and other SAARC economies. Methodology : The study utilized time series data from 1996 to 2021 and employed the trade intensity index (TII), trade complementarity index (TCI), and revealed comparative advantage (RCA) index. Findings : The TII revealed that SAARC economies offered a stable and substantial export market for most of the commodities of Indian origin, but the converse is less favorable, except for the commodities of Nepal’s origin. The RCA index demonstrated the feasibility of bilateral trade between the countries because certain commodities in which one country has a comparative advantage align somewhat with the comparative disadvantage of the other. The TCI highlighted that India has the potential, to a certain extent, to fulfill the import needs of SAARC economies, while other members face a significant deficit in this regard. Practical Implications : The study emphasized the importance of addressing trade barriers and promoting cooperation within SAARC to maximize regional trade. Harnessing comparative advantages and promoting trade complementarity could unlock avenues for economic growth and development for SAARC economies. Originality : To the best of our knowledge, more studies are needed to identify the commodities with future trade potential between India and other SAARC economies. Therefore, our study attempted to fill this gap and contribute to the limited literature in this direction.